VD_FINDINFO HC / 2015 / 37 vom 6. Januar 2015 - VD Tribunal cantonal (2015)
AVANCE DE FRAIS, EXPERTISE, PREUVE À FUTUR, POUVOIR D'APPRÉCIATION | 102 CPC (CH), 103 CPC (CH), 158 al. 1 CPC (CH), 98 CPC (CH)